Building Fashion Customer Loyalty through Brand Awareness and Social Media Marketing: The Mediating Role of Brand Trust and Moderating Brand Reputation - Elya Surya Nugraha; Nur Laili Fikriah (Universitas Mercu Buana, 2026)
Objectives: This study examines how Brand Awareness and Social Media Marketing influence Brand Loyalty among Uniqlo consumers in Indonesia by investigating the mediating role of Brand Trust and the moderating role of Brand Reputation. The study also addresses the empirical inconsistency regarding the direct and moderating roles of Brand Reputation in developing customer loyalty within the fashion retail industry. .Methodology: This study employed a quantitative explanatory survey using a purposive sampling technique. The respondents consisted of 250 Uniqlo consumers in Indonesia who had purchased Uniqlo products at least twice through online or offline channels. Data were collected using a structured online questionnaire distributed through Google Forms and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0.Finding: Results show that brand awareness has a direct positive impact on brand loyalty as well as an indirect impact via brand trust. Similarly, social media marketing has a direct effect on brand loyalty through brand trust. Brand Trust turned out to be the strongest predictor of Brand Loyalty. Additionally, it was found that brand reputation had a negative effect on brand loyalty but a positive moderating effect on the relation between brand trust and brand loyalty.Conclusion: The findings demonstrate that Brand Trust is the central mechanism linking Brand Awareness and Social Media Marketing to Brand Loyalty. While Brand Reputation alone does not directly enhance customer loyalty, it reinforces the positive influence of Brand Trust on Brand Loyalty. Therefore, fashion retailers should prioritize strategies that strengthen consumer trust through consistent product quality, transparent communication, and meaningful customer engagement while maintaining a favorable Brand Reputation to support long-term customer loyalty.